Etiological diagnosis of prostatitis: current methods and ethical evaluation - Manna, Raffaele; Migliore, Alberto (Medicina e Morale, 2024)
The incidence of acute and chronic bacterial prostatitis in the juvenile and adult population is steadily increasing. This phenomenon is related to changing sexual habits. The clinical diagnosis of acute prostatitis is quite simple, both because of the characteristic symptomatology (fever with chills, sacral rachialgia, perineal pain) and the semeiological data of the rectal exploration. Prostate ultrasound may finally help to settle a doubt.